2022
DOI: 10.1007/s12015-022-10335-x
|View full text |Cite
|
Sign up to set email alerts
|

HGF Secreted by Mesenchymal Stromal Cells Promotes Primordial Follicle Activation by Increasing the Activity of the PI3K-AKT Signaling Pathway

Abstract: Primordial follicle activation is fundamental for folliculogenesis and for the maintenance of fertility. An effective therapeutic strategy for patients with premature ovarian insufficiency (POI) is to promote the activation of residual primordial follicles. The secretome of human umbilical cord mesenchymal stromal cells (hUC-MSC-sec) contains several components that might promote the activation of primordial follicles. In the present study, we revealed that treatment with the hUC-MSC-sec significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Xin Mi et al also found that the secretome of hUMSCs helped effectively to activate primordial follicle both in vivo and vitro. And furthermore, hUMSCs-derived HGF upregulated the expression of KIT ligand in GCs, thereby promoting the activation of PI3K/Akt signaling pathway in dormant oocytes (194). Li Z et al revealed that hUMSCs-derived exosome significantly ameliorated ovarian function and reproductive ability of POF mice models through promoting GCs proliferation via the Hippo signaling pathway (195).…”
Section: Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Xin Mi et al also found that the secretome of hUMSCs helped effectively to activate primordial follicle both in vivo and vitro. And furthermore, hUMSCs-derived HGF upregulated the expression of KIT ligand in GCs, thereby promoting the activation of PI3K/Akt signaling pathway in dormant oocytes (194). Li Z et al revealed that hUMSCs-derived exosome significantly ameliorated ovarian function and reproductive ability of POF mice models through promoting GCs proliferation via the Hippo signaling pathway (195).…”
Section: Exosomesmentioning
confidence: 99%
“…also found that the secretome of hUMSCs helped effectively to activate primordial follicle both in vivo and vitro. And furthermore, hUMSCs-derived HGF upregulated the expression of KIT ligand in GCs, thereby promoting the activation of PI3K/Akt signaling pathway in dormant oocytes ( 194 ). Li Z et al.…”
Section: Exosomesmentioning
confidence: 99%
“…The lifespan of the ovary depends on the delicate balance between the survival and death of oocytes. PMF activation is the basis for ovarian folliculogenesis and maintenance of fertility (121). However, damage during ovarian folliculogenesis, including the activation, recruitment, and development of early follicles, has a complex relationship with ovarian aging.…”
Section: Potential Mechanism Of Ovarian Agingmentioning
confidence: 99%
“…A study revealed that the ovarian reserve function of rats' was improved and the number of follicles rose after receiving transplantation human umbilical cord mesenchymal stem cells (hUCMSCs) (115). The hepatocyte growth factor, which is secreted from hUCMSCs, can increase the activity of the PI3K/Akt signaling in dormant oocytes (116). By transplanting hUCMSCs into mice with POF, Lv et al (120) found that multiple hUCMSCs transplantations had a better effect on the recovery of ovarian function than single hUCMSCs transplantation (120).…”
Section: Signaling Pathway and Stem Cellsmentioning
confidence: 99%